Different phenotype of left atrial function impairment in patients with hypertrophic cardiomyopathy and hypertension: comparison of healthy controls - Li, Hongwen; Wang, Haibao; Wang, Tingting; Jin, Chaolong; Lu, Minjie; Liu, Bin (Frontiers in Cardiovascular Medicine, 2023)
Background The impairment of atrial function and atrial-ventricular coupling in diseases with left ventricular (LV) hypertrophy has been increasingly recognized. This study compares left atrium (LA) and right atrium (RA) function, as well as LA-LV coupling, in patients with hypertrophic cardiomyopathy (HCM) and hypertension (HTN) with preserved LV ejection fraction (EF), using cardiovascular magnetic resonance feature tracking (CMR-FT). Methods Fifty-eight HCM patients, 44 HTN patients, and 25 healthy controls were retrospectively enrolled. LA and RA functions were compared among the three groups. LA-LV correlations were evaluated in the HCM and HTN groups. Results LA reservoir (LA total EF, ɛs, and SRs), conduit (LA passive EF, ɛe, SRe), and booster pump (LA booster EF, ɛa, SRa) functions were significantly impaired in HCM and HTN patients compared to healthy controls (HCM vs. HTN vs. healthy controls: ɛs, 24.8 ± 9.8% vs. 31.3 ± 9.3% vs. 25.2 ± 7.2%; ɛe, 11.7 ± 6.7% vs. 16.8 ± 6.9% vs. 25.5 ± 7.5%; ɛa, 13.1 ± 5.8% vs. 14.6 ± 5.5% vs. 16.5 ± 4.5%, p < 0.05). Reservoir and conduit functions were more impaired in HCM patients compared to HTN patients (p < 0.05). LA strains demonstrated significant correlations with LV EF, LV mass index, LV MWT, global longitudinal strain parameters, and native T1 in HCM patients (p < 0.05). The only correlations in HTN were observed between LA reservoir strain (ɛs) and booster pump strain (ɛa) with LV GLS (p < 0.05). RA reservoir function (RA ɛs, SRs) and conduit function (RA ɛe, SRe) were significantly impaired in HCM and HTN patients (p < 0.05), while RA booster pump function (RA ɛa, SRa) was preserved. Conclusions LA functions were impaired in HCM and HTN patients with preserved LV EF, with reservoir and conduit functions more affected in HCM patients. Moreover, different LA-LV couplings were apparent in two different diseases, and abnormal LA-LV coupling was emphasized in HTN. Decreased RA reservoir and conduit strains were evident in both HCM and HTN, while booster pump strain was preserved.